2022
DOI: 10.1177/20406207211066166
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphoma in the United States, 1975–2017

Abstract: Background: Primary central nervous system lymphoma (PCNSL) has received more attention because of an inferior prognosis. Less is known about the incidence rate, histological type, and survival rate of PCNSL, especially in the 2010s. Methods: Data of PCNSL from the Surveillance, Epidemiology, and End Results (SEER) registry database (SEER 9 registries and SEER 18 registries) were used. Incidence was estimated by age, gender, race, site, and histological type. Trends were analyzed using joinpoint regression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Primary intraocular lymphoma (PIOL) is a rare heterogeneous malignancy and considered a subset of primary central nervous system lymphoma (PCNSL), with lymphoma cells initially existing only in the eyes [1,2]. As PIOL is a rare subset of PCNSL, most of its epidemiology data are deduced from studies on PCNSL, whose incidence rate has increased fivefold over the past 40 years, with its peak incidence occurring in those aged 75-84 years [3][4][5]. Between 15 to 25% of PCNSL patients have or will eventually develop ocular lymphoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…Primary intraocular lymphoma (PIOL) is a rare heterogeneous malignancy and considered a subset of primary central nervous system lymphoma (PCNSL), with lymphoma cells initially existing only in the eyes [1,2]. As PIOL is a rare subset of PCNSL, most of its epidemiology data are deduced from studies on PCNSL, whose incidence rate has increased fivefold over the past 40 years, with its peak incidence occurring in those aged 75-84 years [3][4][5]. Between 15 to 25% of PCNSL patients have or will eventually develop ocular lymphoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the 5-year survival rate of lymphomas in the ileocecal region was found to be 64.3% which is higher than that in large intestine (48.8%) and small intestine (32.5%) [17]. Primary central nervous system lymphoma on the other hand showed a low 5-year survival rate of 18% [18]. at being said, appendicular lymphomas have a good prognosis as it was shown that low-grade tumors including lymphomas have a 5-year survival rate of 67%-97% [19].…”
Section: Discussionmentioning
confidence: 96%
“…2 In recent years PCNSL has shown a notable increase in incidence, reaching 0.5 per 100,000 people in immunocompetent patients. 3 Over the last three decades there has been signi cant progress in treatments and prognosis due to insightful retrospective series, single-arm phase II trials, and a set of randomized trials that have collectively contributed to the establishment of treatment guidelines. 4 Another even more rare entity is lymphoma con ned to the blood vessels within the CNS, intravascular lymphoma (IVL).…”
Section: Introductionmentioning
confidence: 99%